(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This article analyzes the activities of internal affairs bodies in ensuring information security from the perspective of social philosophy. The study, based on M. Weber’s theory of legal-rational legitimacy, reveals the powers of internal affairs bodies in the information space, their legality and social validity. At a time when the role of state institutions in ensuring security is increasing in the context of the information society, the issue of the institutional status of internal affairs bodies and their legitimate functioning through legal mechanisms is becoming relevant.